The International VLBI Service in its transition to VGOS - McCallum, L. (2025)
The International VLBI Service for Geodesy and Astrometry (IVS) coordinates global VLBI observations for the main products of the terrestrial and celestial reference frame as well as Earth orientation parameters. Driven by the need for higher accuracies as well as an increasingly crowded frequency spectrum in the S-band, the IVS is currently transitioning to its new VLBI Global Observing System (VGOS). VGOS encompasses new frequencies (314 GHz) and largely new infrastructure, ultimately aiming for one order of magnitude improvement in the results compared to the legacy S/X system. This contribution features the status of the VGOS roll-out, current and future operations and results. IVS products will be discussed, in particular, in terms of cadence and turn-around times as well as their incorporation into wider geodetic and astrometric products.